Analisis Hubungan Simultan Pertumbuhan Ekonomi, Pendidikan, dan Pengangguran terhadap Kemiskinan Sumatera Barat - Hadi, M. Asyrafi; Andrianus, Fery (Jurnal Informatika Ekonomi Bisnis, 2025)
In 2023, the percentage of poverty in the Province of Sumatra increased from the previous year to 5.95%, which reflects the unequal distribution of economic growth and access to basic services in this area. This study aims to analyze the simultaneous effect of economic growth, education, and unemployment rates on poverty in 19 districts/cities in West Sumatra during the period 2014–2023. The method used is a quantitative approach with the Panel Vector Error Correction Model (PVECM) which allows the identification of short-term and long-term relationships between variables. The results of the study show that in the long term education has a negative and significant effect on poverty, meaning that improving the quality of education can reduce poverty levels, while economic growth has a positive and significant effect on poverty in West Sumatra, and unemployment in the long term does not have a significant effect on poverty. In the short term, the education and unemployment variables do not have a significant effect on poverty, while economic growth in lag 1 has a negative and significant effect on poverty and a positive effect on poverty in lag 2.